Impact of Substance Use and Mental Health Comorbidity on Health Care Access in Canada. Issue 4 (2nd October 2019) - Đào, Grace J.; Brunelle, Caroline; Speed, David
Abstract: Objective: Psychological disorders and substance use comorbidity is associated with greater symptomatology and a worse prognosis. Previous research has highlighted discrepancies in the level of use of health care services in individuals experiencing comorbidity compared to those with mental disorders or substance use disorders alone. The purpose of the current study was to compare mental health service use (i.e., access, number of professionals accessed, helpfulness of services received, and number of hours of services received) among individuals with mental disorders, substance use disorders, and comorbid disorders. Methods: Participants consisted of respondents to the 2012 Canadian Community Health Survey-Mental Health ( N  = 25, 133). The researchers used a mixture of binary logistic regressions, Poisson regressions, linear regressions, and ordinal logistic regression to explore the impact of demographic variables, psychological distress, and clinical categories on health care access. Results: The mental disorders group, OR  = 0.52, p  = .008, 95% CI [0.32, 0.85], d  = 0.36, and the substance use disorders group, OR  = 0.31, p = .001, 95% CI [0.16, 0.60], d  = 0.65, were significantly less likely than the comorbid group to report having accessed a professional in the past year. There were no significant differences in the perceived level of helpfulness for interventions received or in the time spent in professional consultation when comparing the substance use disorders and mental disorders groups to the comorbid group. Conclusions: Although the level of access to health care was low overall, those with concurrent disorders were more likely to access mental health services than those with substance use disorders or mental disorders only. The findings of this study reveal various treatment gaps, especially in those experiencing substance use disorders, and reaffirm the importance of improving treatment accessibility for these individuals.